Exploring the possibilities of using cryptocurrencies in production in creative industries - A. R. Akopyan; Yu. V. Vorontsova; V. V. Krysov (Вестник университета)
In the modern world, cryptocurrencies are widely used in various economic sectors. One of the advantages of applying this type of currency is the ability to conduct fast and secure financial transactions without the involvement of intermediaries. Cryptocurrency can become an incentive for the development of new business models and creation of new opportunities for small and medium entrepreneurs. The purpose of the study is to determine the potential of applying cryptocurrencies in creative industries as well as possibility of using their advantages. Almost everyone in society is a user and potential creator of intellectual activity. Its protection through a system of national and international rules called intellectual property rights is necessary to ensure financing of innovations and creativity, which, in turn, leads to economic, cultural and social progress. Intellectual property protection also contributes to the production and dissemination of knowledge and a wide range of high-quality goods and services. Copyright is the main method of prevention of piracy and theft of intellectual property. Studying the prospects of using cryptocurrency in production in creative industries is necessary to make its formation as an important tool in this area possible.